PELATIHAN PEMANFAATAN TEKNOLOGI CHATGPT UNTUK SURAT MENYURAT KADER PKK DESA CIMULANG BOGOR - Marlinda, Linda; Gata, Windu; Tutupoly, Taransa Agasya (LPPM Universitas Nusa Mandiri, 2024)
The use of technology is the key to increasing effectiveness and efficiency in communication. One technology that is currently developing is chatbot, a computer program that can interact with humans via chat or text messages. Chatbots can speed up the flow of communication, simplify information retrieval, and increase the level of community involvement in various activities. Training in the use of ChatGPT Technology for writing correspondence is important considering the need for efficiency and quality in written communication, especially for Village PKK cadres. This training aims to improve cadres' ability to use ChatGPT technology to compose correspondence more effectively and efficiently. With this training, several significant outcomes were achieved. First, there will be an increase in productivity in the preparation of official and informal letters by Village PKK cadres, because the use of ChatGPT technology will speed up the process of writing and sending letters. Second, it can improve the quality of cadres' written communication, so that the message conveyed can be more clearly and effectively understood by the recipient. Lastly, the use of ChatGPT Technology can expand the scope of messages delivered to the people of Cimulang Village, Bogor, so that important information and education can be broader and more easily accessible to all residents. This training not only supports the efficiency and quality of communication but also strengthens relations between cadres and society as a whole.